Hubungan Antara Kepemimpinan Manajerial Kepala Sekolah Dan Kompensasi Dengan Kepuasan Kerja - irfan mujahid; Marjuki Aljawi (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
The objective of this researdh is to find out the correlation between Principal’s Managerial Leadership and Compensation as independent variables with Job Satisfaction as dependent variable, both individually and collectivelly. Among 119 vocational high school teachers were surveyed and 77 respondent were selected as samples for the research. Normality, simple regression, multiple regression, simple correlation, multiple correlation, and partial correlation are several data analysis method that were used in this research. The result of this research imply that: Firstly, a positive and significant corelation was found between Principal’s Managerial Leadership with Job Satisfaction and expressed in coefficient correlation correlation ry1 = 0.0,319 (a = 0,05) and regression equation as Y=94,350 + 0,245X1 and determination coefficient is r2y1 = 0.101 Secondly, a positive and significant corelation was found between Compensation and Job Satisfaction can be found and expressed in coefficient correlation ry2 = 0.314 and regression equation as Y = 98,752 +0,205X2 and determination coefficient is r2y2 = 0.099. Thirdly, this research also found that there is a positive corelation between Principal’s Managerial Leadership and Compensation along with Job Satisfaction which is expressed in multiple correlation of ry12 = 0.319 and regression form of Y= 94,709 +0,219X1 + 0,023X2, and determination coefficient is r2 = 0,319 . According to result of this research that improvement of teachers job satisfaction can be in creased by Principal’s Managerial Leadership interest and Compensation interest.